Analysis Of Communication And Teamwork On Employee Performance With Increased Synergy As An Intervening Variable At Bpjs Padang Sidempuan Raya Branch And Pematang Siantar Raya Branch Offices - YUNITA BR HUTAURUK; Isa Indrawan (International Journal of Society and Law, 2024)
In this research, the researcher aims to see the results of the influence of communication and teamwork on employee performance by synergy as an intervening variable at the BPJS Padang Sidempuan Raya and Pematang Siantar Raya branch offices. The phenomenon that occurred at the Padang Sidempuan Raya and Pematang Siantar Raya branch offices was the influence of communication and teamwork on employee performance with increased synergy as an intervening variable at the Padang Sidempuan Raya and Pematang Siantar Raya branch offices. Where communication is very important in employee performance to increase synergy and cooperation within the team. When communication and teamwork work poorly, employee performance in improving company synergy will be delayed. So a good relationship between communication and teamwork is needed to build synergistic performance. The results of this research are as follows: Teamwork has a positive and significant effect on employee performance with a value of 0.177 and a significant value of 0.005. Teamwork has a positive and significant effect on synergy with a value of 0.196 and a significant value of 0.023. Communication has a positive and significant effect on employee performance with a sample of 0.259 and a sig of 0.016. Communication has a positive and significant effect on Synergy with a value of 0.733 and a sig of 0.000. Synergy has a positive and significant effect on employee performance with a value of 0.533 and a significant value of 0.000. Teamwork has a positive and significant effect on employee performance indirectly through Synergy with a value of 0.104 and a significant value of 0.041. Communication has a positive and significant effect on employee performance indirectly through Synergy with a value of 0.391 and a significant value of 0.000